BODIPY–diketopyrrolopyrrole–porphyrin conjugate small molecules for use in bulk heterojunction solar cells. Issue 18 (24th April 2018) - Bucher, Léo; Desbois, Nicolas; Koukaras, Emmanuel N.; Devillers, Charles H.; Biswas, Subhayan; Sharma, Ganesh D.; Gros, Claude P.
Abstract : Two small molecules denoted asBD-pPor andBD-tPor composed of a central BODIPY core surrounded with two DPP and two porphyrin units have been designed and synthesized. Abstract : Two small molecules denoted asBD-pPor andBD-tPor composed of a central BODIPY core surrounded with two DPP and two porphyrin units have been designed and synthesized. InBD-pPor andBD-tPor, porphyrins are linked to the central BODIPY by phenyl and thiophene bridges, respectively. The optical and electrochemical properties were systematically investigated in order to employ them as donors along with PC71 BM as an acceptor for solution processed bulk heterojunction organic solar cells. After the optimization of the active layer, the organic solar cells based onBD-pPor andBD-tPor exhibit overall power conversion efficiencies of 6.67% and 8.98% with an energy loss of 0.63 eV and 0.50 eV. The low value of energy loss forBD-tPor may be related to the low LUMO offset between theBD-tPor and PC71 BM (0.31 eV) as compared to that betweenBD-pPor and PC71 BM (0.36 eV). The low energy loss also leads to a higher value of open-circuit voltage for theBD-tPor based OSC than itsBD-pPor counterpart, despite the slightly deeper HOMO energy level ofBD-pPor . The enhanced values of J sc and FF of theBD-tPor based OSCs may be related to the better exciton dissociation and charge transport, as confirmed from the PL spectra and charge carrier mobility. These results indicate that the combination of BODIPY, DPP and porphyrin in the same conjugate is very promising for small molecule organic solar cells.